2022
DOI: 10.1073/pnas.2208058119
|View full text |Cite
|
Sign up to set email alerts
|

T cell and B cell antigen receptors share a conserved core transmembrane structure

Abstract: The B cell and T cell antigen receptors (BCR and TCR) share a common architecture in which variable dimeric antigen-binding modules assemble with invariant dimeric signaling modules to form functional receptor complexes. In the TCR, a highly conserved T cell receptor αβ (TCRαβ) transmembrane (TM) interface forms a rigid structure around which its three dimeric signaling modules assemble through well-characterized polar interactions. Noting that the key features stabilizing this TCRαβ TM interface also appear w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 94 publications
1
1
0
Order By: Relevance
“…However, three groups have recently determined the full-length transmembrane structures of the BCR using cryo-EM [16,17,19]. These studies of the murine IgM BCR [19], the human IgG BCR and IgM BCR [16], and a second study of the human IgM BCR (Figure 2) [17], confirmed previous biochemical, fluorescence resonance energy transfer, computational modelling and experimentally guided modelling [31][32][33], showing the F ab arms in a Y shape free of the CD79a/CD79b heterodimer bound to the mIg F c domain with 1:1 stoichiometry [34]. The CD79a/CD79b heterodimer consists of an extracellular domain, a linker and a transmembrane domain.…”
Section: B Cell Receptor Structuresupporting
confidence: 59%
See 1 more Smart Citation
“…However, three groups have recently determined the full-length transmembrane structures of the BCR using cryo-EM [16,17,19]. These studies of the murine IgM BCR [19], the human IgG BCR and IgM BCR [16], and a second study of the human IgM BCR (Figure 2) [17], confirmed previous biochemical, fluorescence resonance energy transfer, computational modelling and experimentally guided modelling [31][32][33], showing the F ab arms in a Y shape free of the CD79a/CD79b heterodimer bound to the mIg F c domain with 1:1 stoichiometry [34]. The CD79a/CD79b heterodimer consists of an extracellular domain, a linker and a transmembrane domain.…”
Section: B Cell Receptor Structuresupporting
confidence: 59%
“…The linker peptide (Lµ B ) passes through an "O-ring" formed between CD79a and CD79b that introduces the ECD into the plasma membrane [16,17], where the TM helices form a compact bundle dominated by van der Waals forces and several hydrogen bonds [16,17,19]. Connecting the IgM linker region to CD79a/CD79b though a space in the heterodimer supports the theory that the BCR is assembled in the endoplasmic reticulum [31]. The cytoplasmic tails of the BCR subunits were not identified, suggesting that they are structurally flexible and difficult to characterize using cryo-EM.…”
Section: B Cell Receptor Structurementioning
confidence: 72%
“…Adaptive immunity is mediated by repertoires of T cell receptors (TCRs) and B cell receptors (BCRs) expressed on the surfaces of T and B cells, respectively 11 . Due to somatic recombination of V(D)J genes, the potential diversity of adaptive immune receptor repertoires far exceeds the number of B or T cells in any one individual.…”
Section: Introductionmentioning
confidence: 99%